Kontinuitas Kebijakan dan Pemberdayaan Masyarakat di Kalurahan Dadapayu Kapanewon Semanu Kabupaten Gunungkidul - Analius Giawa, Rukoyah (Program Studi Pembangunan Masyarakat Desa (D3), 2021)
A policy becomes a key in development management from central, regional and village level. The policy as a reference towards development management. Rural areas have become the government’s priority in pushing the acceleration of poverty alleviation. It is because the highest poverty base is still found in rural areas. The Data of National Statistical Central Burau indicates that the poverty level in rural areas is 12.5%. Various policy products and empowerment activities performed in the area are aimed to strengthen the capacity, push development and alleviate poverty. However, many policies are unable to answer issues which occur in societies. Therefore, the continuity of policy that has existed in Kalurahan Dadapayu Semanu should be reviewed. The analysis result indicates that Human resource obstacle has become an obstacle that influences the process of policy making. Empowerment activities which are still performed focus on the activities themselves but there has not been an analysis towards activity from upstream to downstream. It is also caused by the weak evaluation performed towards the policy products in Kalurahan Dadapayu.